2012
DOI: 10.1088/2043-6262/3/3/033001
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide-based conjugates for cancer theragnostics

Abstract: In this paper we first summarize our recent research on fabrication and structure characterization of conjugates of Fe3O4 nanoparticles (MNPs) encapsulated by several organic materials such as oleic acid (OL), starch (ST), dextran (D), chitosan (CS), O-carboxymethyl chitosan (OCMCS) and the copolymer of poly(styrene-co-acrylic acid (St-co-AA)). The ferrofluids stability and toxicity were also considered. The magnetic inductive heating (MIH) curves were measured using a set up with an alternating (ac) magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Experiments were performed in a custom-made setup that comprised a parafilm-covered plastic Eppendorf tube or glass vial containing the MNP sample, fibre-optic temperature measurement probes (Luxtron FOT Lab Kit, accuracy 0.2 °C, sample frequency 1 Hz), and a water-cooled solenoid magnetic coil attached to a Magnetic AC Hyperthermia (MACH) system made by Resonant Circuits Ltd. Figure 2 shows a schematic drawing of the setup used, which conforms to published descriptions of 'a typical experimental setup' [14]. Indeed, many groups working on SAR/ILP measurements report similar non-adiabatic systems in their publications (e.g [18,22,24,26,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].). Some groups surround their samples with holders of varying insulating strengths, such as Styrofoam or other thermally insulating materials, while others do not [27].…”
Section: Measuring Sar/ilp: Experimental Considerationsmentioning
confidence: 83%
“…Experiments were performed in a custom-made setup that comprised a parafilm-covered plastic Eppendorf tube or glass vial containing the MNP sample, fibre-optic temperature measurement probes (Luxtron FOT Lab Kit, accuracy 0.2 °C, sample frequency 1 Hz), and a water-cooled solenoid magnetic coil attached to a Magnetic AC Hyperthermia (MACH) system made by Resonant Circuits Ltd. Figure 2 shows a schematic drawing of the setup used, which conforms to published descriptions of 'a typical experimental setup' [14]. Indeed, many groups working on SAR/ILP measurements report similar non-adiabatic systems in their publications (e.g [18,22,24,26,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].). Some groups surround their samples with holders of varying insulating strengths, such as Styrofoam or other thermally insulating materials, while others do not [27].…”
Section: Measuring Sar/ilp: Experimental Considerationsmentioning
confidence: 83%
“…In the recent decade, with the rapid development of nanotechnology, many nanoparticles and nanocomposites have been studied toward applications in treatment for endangering diseases or environments [8,9]. Among them, silver and its compounds have been used extensively in many bactericidal applications [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the fluctuations of the electron density in the electron gas can be described by a scalar field whose quanta are the elementary collective excitations called plasmons-the plasmon field. The present work is the continuation of the previous one [64].…”
Section: Conclusion and Discussionmentioning
confidence: 55%
“…In order to overcome the difficulties related to the complicated geometrical forms of the plasmonic structures, it was proposed to apply the functional integral technique using the integration and the integral equations instead of the differentiation and the differential equations in traditional quantum mechanics [64]. The formulation of the physical problems mainly in terms of the integration and the integral equations facilitates the elaboration of computational methods.…”
Section: Introductionmentioning
confidence: 99%